MEMAHAMI KETIMPANGAN INFORMASI DI ERA GLOBALISASI - Kartini (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2017)
This article will discuss about understanding information inequality in society when entering the era of globalization. Indeed, with the advancement of such a great communication technology, then each member of the world community can work together, compete and compete with each other freely. Geographical isolation and distant distances are no longer an obstacle. From an economic point of view, after the ASEAN free market (AFTA), we also witnessed the Asia-Pacific free market (APEC) and the last free world market (WTO). But because the power of capital, human resources, management, technology and industry controlled by the North countries, resulting in unfair competition. In this case, especially Indonesia, let alone for world level, ASEAN level we are still difficult to win the competition. So also in terms of culture, various ideologies, understandings and lifestyle will affect each other quickly, quickly change the community order. Once again, although theoretically all members of the world community influence each other, but due to unbalanced forces, which will dominate and impose its view is the Western countries. As an illustration, if we go to Europe or America, we can be sure we will not be able to watch television shows from Indonesia. But instead if we open any Indonesian TV station, we will easily get the events of Western products.